IMAGING OF COMPLEX BASIN STRUCTURES WITH THE COMMON REFLECTION SURFACE (CRS) STACK METHOD - Menyoli E.; Gajewski D.; Hübscher C. (My University, 2004)
Common reflection surface (CRS) stack technology is applied to seismic data from certain areas of the Donbas Foldbelt, Ukraine, after conventional seismic methods gave unsatisfactory results. On the conventionally processed post-stack migrated section the areas of interest already showed clear features of the basin structure, but reflector continuity and image quality were poor. It was our objective to improve the image quality in these areas to better support the geological interpretation and the model building. In contrast to the standard common mid-point (CMP) stack, in which a stacking trajectory is used, the CRS method transforms pre-processed multicoverage data into a zero-offset section by summing along stacking surfaces. The stacking operator is an approximation of the reflection response of a curved interface in an inhomogeneous medium. The primary advantage of the data-driven CRS stack method is its model independence and the enhancement of the signal-tonoise ratio of the stacked sections through a stacking reflection response along traces from more than one CMP gather. The presented results show that the multifold strength of the CRS stack is of particular advantage in the case of complex inverted features of Devonian‐Carboniferous sediments in the Donbas Foldbelt data. We observe that in these areas where the confidence level for picking and interpretation of the stacking velocity model is low, imaging without a macrovelocity model gives improved results, because errors due to wrong or poor stacking velocity models are avoided.
Keywords: common reflection surface stack; foldbelt; inverted structures